2018
DOI: 10.1111/nep.13008
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in TTC21B cause different phenotypes in two childhood cases in China

Abstract: Mutations in TTC21B cause a range of ciliopathy phenotypes in humans. We identified 3 novel TTC21B mutations in two Chinese paediatric cases that both presented end-stage renal disease and other different features. This is the first TTC21B mutations ever reported in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
0
16
0
1
Order By: Relevance
“…Zhang et al, reported one pediatric case with mild cytolysis and one with hepatosplenomegaly, both associated with NPHP. Cong et al, described a case of biliary cirrhosis and one case of chronic chilestasis (5,12). An association of congenital hepatic fibrosis with NPHP or JATD has also been reported (13).…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…Zhang et al, reported one pediatric case with mild cytolysis and one with hepatosplenomegaly, both associated with NPHP. Cong et al, described a case of biliary cirrhosis and one case of chronic chilestasis (5,12). An association of congenital hepatic fibrosis with NPHP or JATD has also been reported (13).…”
Section: Discussion and Review Of The Literaturementioning
confidence: 99%
“…This suggests that the ratio of urinary α1-microglobulin to microalbumin could be used to measure LMWP in urine in patients with NPHP. However, albuminuria in the nephrotic range is also seen in a few patients with NPHP (26), and LMWP in urine is not always specific to NPHP. NS, IgA nephropathy, Henoch-Schonlein purpura nephritis, and lupus nephritis are the most common glomerular diseases that present during childhood.…”
Section: Resultsmentioning
confidence: 99%
“…This protein is required for retrograde intraflagellar transport in the cilium. Mutations in the TTC21B gene have been pro-posed to be associated with various ciliary dysfunctions [36]. A study on massive parallel sequencing in patients with glomerular and cystic kidney diseases revealed that myopia was present in 5 of 23 patients (22%), two of whom had high myopia [37].…”
Section: Discussionmentioning
confidence: 99%